Analysis of E-commerce Based on Digital Economy through Smart Society in the Management of Village-Owned Enterprises - Neks Triani; Mardiana; Muhammad Fath Azzajjad; Dewi Satria Ahmar (PT Mattawang Mediatama Solution, 2023)
This research is descriptive research to describe the reality and complexity of social e-commerce based on the digital economy through the smart society of village-owned enterprises in Tanggetada District, using a purposive sampling technique. The research will be conducted in 3 village offices in Tanggetada Sub-district, namely Tondowolio, Palewai, and Lamedai villages. The research instruments are observation, questionnaire, interview, and documentation. Smart society measurement is carried out by observing and collecting information using the ecosystem of village-owned enterprises related to community welfare and the ecosystem of financial transactions of village-owned enterprises. The results of the study obtained that the three villages in Tanggetada sub-district have village-owned business entities with various types of businesses that have been run, basically, the three villages have planned the development of e-commerce in a sustainable manner, based on information showing that in general, the Smart Society Analysis Mapping in Tanggetada Sub-district is at >2.5 to 3.25 (Good), a humanist and dynamic relationship is realized in the socio-cultural and socio-technical community as a reference for the creation of productivity, communicative, and interactive with digital systems both physical and virtual in harmony. The creative economy has contributed to exploring the potential in raising the level of the creative economy in the Tanggetada sub-district.